Strategi Pemasaran Agrowisata Royal Cocoa sebagai Wisata Edukasi di Banjar Wongaya Beten Mengesta Kecamatan Penebel Kabupaten Tabanan - Ni Luh Gde Hita Rihati; Ida Ayu Tary Puspa; I Ketut Wardana Yasa (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2019)
Based on this research, Royal Cocoa Agrotourism as Educational Tourism has good tourism potential to be marketed. But, this tourism has not maximized its marketing in market expansion and technology. So, This research is aimed to recognize the marketing strategy of Royal Cocoa Agrotourism located in Banjar Wongaya Betan. The method used in the research is qualitative and quantitative research (mixed methods) using marketing theory and consumer theory. Data collected through observation, interviews, questionnaires, documentation and literature study. Then the data is analyzed using discussing Internal External, SWOT Analysis, and satisfaction analysis. The results of this research indicate that the analysis of the internal-external matrix (IE) the position of Royal Cocoa Agro Tourism is in cell IV where it grows and builds. While based on the SWOT analysis, the strategies that can be formulated are as follows: Promotion of Technology-Based Media, Improving road access, Increasing the Government's role, and Increasing cooperation with other parties. While the data analysis of tourist satisfaction towards tourists is less satisfied with the marketing ofThe Royal Cocoa Tourism Agro. Therefore, the marketing strategy in Royal Cocoa to increasing the level of visits in meeting tourist satisfaction is recommended using grand strategy and alternative strategies that have been formulated in this research.